PENDAMPINGAN PROSES PRODUK HALAL BAGI PRODUK RUMAHAN PADA MAHASISWA FEBI DALAM MENINGKATKAN KESADARAN HALALISASI PRODUK - Wasisman, Zeti Agesti; Asnaini, Asnaini; Yustati, Herlina (JURNAL ILMIAH EDUNOMIKA, 2025)
Law number 33 of 2014 concerning halal product guarantees will begin to be implemented on october 17 2024, which requires Halal certification for three product categories, on of which is food and beverages. To support this initiative, the Halal Product Guarantee Organizing Agency (BPJPH) from the ministry of Religion has launched a free Halal Certification Program (SEHATI) 2023, by Providing a quota of Million for micro and small enterprises (UMK).Fatmawati Sukarno state Islamic University Bengkulu has several students who have a home-madeprocessed product business, be it food or drinks in several faculties, namely the faculty of islamic Economics and Business, the Faculty of Tadris and Tarbiyah, The Faculty of Ushuluddin Adab and Daâ€™wah and the Faculty of Sharia and of Course Various Types of Processed food and drinks that are spread both online and offline sales and use saveral types of muamalah transactions, one of which is using the isthisna contract which means an order contract which means that an item that has been ordered must be produced/processed first. In this case it is a very important thing to guarantee the food or drinks products ordered, because as muslims, of course the most important thing that must be considered in purchasing food and drinks is guaranteed cleanliness, basic ingredients.Â Keywords: Assistance, Halal, ProductÂ